(untitled) (Research, Society and Development, 2023)
Temporomandibular disorder (TMD) consists of a set of signs and symptoms that affect the temporomandibular joint (TMJ). Its etiology is diverse and is often related to biopsychosocial aspects, including sleep quality and emotional factors such as stress and anxiety. The young population is classified, in many studies, as a group with a greater propensity to have TMD, among them are students of the Dentistry course, who, due to exposure to factors that generate stress and anxiety, configure a group with potential risk for the diagnosis of temporomandibular disorders. This study aimed to evaluate the prevalence of dysfunction symptoms among Dentistry students from different periods, in addition to identifying possible correlations with levels of anxiety and stress. The sample consisted of 205 participants who answered sociodemographic questions and three instruments: Fonseca’s Anamnestic Index (for TMD symptoms), Lipp’s inventory (for signs of stress) and Beck’s Anxiety Inventory. After data collection, statistical analysis was performed. It was concluded that, in the studied public, there was a high prevalence of TMD symptoms, mostly mild. The female gender was more affected by TMD, anxiety and stress. There was an association between the presence of TMD symptoms, anxiety levels and stress symptoms, in addition to an association between the degree of TMD severity and the final period of the course. The higher the levels of anxiety and stress, the greater the degree of TMD.